ANALISIS IKLIM ORGANISASI DAN PARTISIPASI DALAM PENGAMBILAN KEPUTUSAN TERHADAP KEPUASAN KERJA GURU SEKOLAH DASAR DI KECAMATAN SUKAJADI KOTA PEKANBARU - Reni Elvina; Mashadi Mashadi; Sumarno Sumarno (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
This Research aims to determine the influence of organizational climate onparticipation in decision making elementary school teachers in Sukajadi District PekanbaruCity, To determine the influence of organizational climate on the job satisfaction of teacherelementary school in District Sukajadi Pekanbaru City, and To know How The influence ofparticipation in decision making on job satisfaction of elementary school teacher in DistrictSukajadi Pekanbaru City. Based on the result of correlation coefficient value betweenorganizational climate influence (X1) to participation in decision making (X2) is equal to 0.957.In the calculation of path coefficient shows the value of coefficient of path on substructure-1 isalso 0.957. While the remaining amount (100% - 95.7 = 4.3%) is influenced by other variablesthat are outside of this research variable. Based on the summary model table, the effect ofOrganizational Climate (X1) and Participation in Decision Making (X2) on Job Satisfaction ofTeacher (Y) is 0.688. While the coefficient of determination is the square of 0.688 is 0.473.The remaining amount (100% - 47.3 = 52.7%) is influenced by other variables that are outsideof this research variable.